Electron Microscope Scanning, and Antibacterial Activity of Tio2 Nanoparticles on pathogenic strains of Staphylococcus aureus and Escherichia coli - Abd Alrazaq Hassan, Manar; Hassan, N.A.; Khudhair Khalaf, Shahad; hakiem tawfieq, Ali (Diyala Journal of Medicine, 2024)
Background: Nanoparticles are increasingly being used as an alternative antibiotic to target microorganisms, particularly for treating bacterial infections. In current study it was recognized processes such as metal ion release, induction of oxidative stress, and non-oxidative mechanisms. Developing resistance to nanoparticles is challenging for bacterial cells due to the multiple simultaneous actions against microorganisms, and require several simultaneous gene alterations within the same bacterial cell. Objective: To determine the effect of the titanium dioxide nanoparticles (TiO2NPs) on the activity of the same bacteria that participate in dental caries (Staphylococcus aureus and Escherichia coli). Patients and Methods: The study included 50 patients who attended the dental clinic and took the samples by the wooden swap from the molar area (cervical area of inflamed gingiva and same samples taken from occlusal surface of molar). The collected samples were cultured on “Mannitol salt agar, Blood agar, and MacConkey's agar plates” for separation of the needed bacteria (Staphylococcus aureus and Escherichia coli) that showed wide spreading in the oral cavities and dental carries. TiO2NPs are then created using pulse laser ablation, followed by coating preparation the nanoparticles materials (using a hybrid sol-gel and organ silicate nanoparticles), and finally the prepared nanoparticles to the coating solution and local paint was used for antimicrobial activity of the separated bacteria using different concentrations of TiO2 in the cultures. Results: Characterization showed the phase of the TiO2NPs was spherical, with very few irregularly shaped particles, and had an average small size in millimeters. Antimicrobial activity results showed a strong bactericidal effect against Gram-positive bacteria and demonstrated greater sensitivity to TiO2 nanoparticles at lower concentrations when compared to Gram-negative bacteria. Conclusion: It was shown that nanotechnology promise in treating various infections caused by bacteria, including dental caries. Notably, nanoparticles have demonstrated broad-spectrum antibacterial effects against Gram-positive bacteria.